Feeding indices and digestive proteolytic activity of pistachio hull borer, Arimania comaroffi (Rogonot) (Lep.: Pyralidae) on five pistachio varieties - S. M. Mansouri; F. Khajeh (نامه انجمن حشره‌شناسی ایران, 2017)
Pistachio hull borer, Arimania comaroffi (Rogonot)(Lep: Pyralidae) is an insect pest which has turn into an outbreak in some pistachio orchards of Rafsanjan. In order to study feeding indices and total proteolytic enzymatic activity, larvae of A. comaroffi were reared on fruits of five pistachio varieties including, Ahmadaghai, Akbari, Ohadi, Kaleghochi and Momtaz at 25±2ºC, 45±5% RH and 16:8 (L:D) h. In each experimental container, one larva at the same initial weight was located on one fruit of each pistachio variety. Every 24 h, fruits were changed and larval weight gain, weight of skin of pistachio's fruit and weigh of larval feces were recorded. The total protein of fruits skin of different pistachio varieties was evaluated as well. Based on the results, the lowest amounts of conversion efficiency of ingested food and conversion efficiency of digested food were in larvae reared on fruit of Ohadi variety and the lowest proteolytic activity was in larvae fed on fruits of Ohadi and Akbari varieties. The highest feeding indices and protease activity were in larvae fed on Momtaz. The lowest protein content of pistachio fruits skin was on Ohadi and Akbari, and the highest content was on Momtaz. There was a positive correlation between protein content of tested varieties and protease activity of larvae. According to the result of cluster analysis, Ohadi, Ahmadaghai, and Akbari varieties had a negative significant effect on feeding efficiency of A. comaroffi larvae as compared with the other varieties.